Inhibition of bronze corrosion in 3%NaCl media by novel non-toxic 3-phenyl-1, 2, 4-triazole thione formulation. (April 2015) - Dermaj, A.; Chebabe, D.; Doubi, M.; Erramli, H.; Hajjaji, N.; Casaletto, M. P.; Ingo, G. M.; Riccucci, C.; de Caro, T.
<x content-type="archive" xml:space="preserve">Abstract</x> Bronzes are largely used in various domains such as battery connectors, archaeological artefacts and urban statues, suffering from corrosion process leading to the formation of corrosion products. A protection treatment could be used to insulate them from this environment. In this way we contribute to the protection of bronze in the environment by use of organic corrosion inhibitors. In this work a novel organic compound (3-phenyl-1·2·4-triazole-5-thione) was tested as a corrosion inhibitor on a pure reference bronze alloy (CNR alloy). The electrochemical behaviour was investigated in 3%NaCl solution, in the presence and absence of the inhibitor formulation using potentiodynamic polarisation and electrochemical impedance spectroscopy (EIS). The obtained results confirm that the compound is a good corrosion inhibitor which acts reduce both cathodic and anodic reactions rates. The inhibiting efficiency was found to be about 97% at 2·5 mM of inhibitor concentration. SEM coupled with EDX and XPS analysis confirms the good protective effect due to the establishment of an inhibitor film on the bronze sample.